OCCUPATION DYNAMICS OF BROMELIADS BY DENDROPHRYNISCUS BREVIPOLLICATUS (ANURA: BUFONIDAE) IN A SANDY PLAIN AREA ON INSULAR ENVIRONMENT, RIO DE JANEIRO, BRAZIL: Life Science-Ecology - CRUZ SOUZA LIMA, MAURO SÉRGIO; PEDERASSI, JONAS; ALBERTO DOS SANTOS SOUZA, CARLOS (International Journal of Life Science and Pharma Research, 2013)
Dendrophryniscus brevipollicatus is a bromeliad anuran that inhabits forests up to 900 meters in the southeastern coast of Brazil. We evaluated the occupation of Neoregelia johannis and Aechmea sp. bromeliads by this species, seeking to verify abiotic factors determining such a choice of occupation. The occurrence of anuran was assessed by the constancy of Bodenheimer (1955). A causal and occupational model was designed using Vensim® software. Seventeen frogs were found in bromeliads, being N. johannis constantly occupied (C = 76.47%) and Aechmea sp. accidentally occupied (C = 23.53%). The causal diagram was consolidated with 22 connectors and four streams connecting the systems, while the model indicated the incidence of light as an element for limiting the occupation of the bromeliad Aechmea sp. In addition to the criteria for bromeliad occupation by anurans, it was observed that D. brevipollicatus does not require, as advised, forests of slopes for its perpetuation, because the sampled population inhabits secondary forest on sandy plain, five meters from the sea level-implying a reclassification of the species regarding its ability for environmental occupation - and also making visible the need for protecting the sandy plain and its secondary vegetation.